Long-term outcomes in COVID-19 patients who recovered from the first wave of the pandemic - Cui, Dan; Chen, Simiao; Feng, Luzhao; Jia, Mengmeng; Wang, Yeming; Xiao, Weijun; Sun, Yanxia; Huang, Qiangru; Ma, Libing; Leng, Zhiwei; Wang, Hao; Cao, Bin; et al. (National Science Review, 2022)
This cross-sectional study evaluated the long-term health effects of coronavirus disease 2019 (COVID-19) in Jianghan District (Wuhan, China). The results showed that 61.4% of COVID-19 patients reported at least one symptom and 8.8% had depressive symptoms at the 17-month follow-up. The proportion of patients with chest radiographic abnormalities in Fangcang shelter hospitals and designated COVID-19 hospitals was 31.6% and 41.1%, respectively, and the proportion of patients with impaired pulmonary diffusion capacity in these hospitals was 52.8% and 60.9%, respectively. Female sex (odds ratio [OR] = 1.48, 95% confidence interval [CI]: 1.16-1.88), severe disease (OR = 1.46, 95% CI: 1.01-2.10) and a higher number of initial symptoms (OR = 1.31, 95% CI: 1.23-1.40) were associated with the development of sequelae symptoms at 17 months. This study involving community-dwelling COVID-19 adults may help determine the long-term effects of COVID-19 during the first pandemic wave. Nonetheless, larger follow-up studies are needed to characterize the post-COVID-19 condition.
Gesehen am 23.01.2023